Strategi Pengembangan Pemasaran Kopi Robusta di Unit Usahatani Agro Semesta - Wartju, Jason Jonathan; Setiawan, I Gede Bagus (Agrisintech (Journal of Agribusiness and Agrotechnology), 2024)
The problem faced by coffee farmer groups in Tabanan Bali is marketing. This is also experienced by the Agro Semesta Farming Business Unit (UUT) located in Pajahan Village, Pupuan District, Tabanan Regency. They still have difficulty in marketing their flagship product, namely Sobean Coffee. This study aims to identify factors in the internal and external environment in marketing development, as well as to find alternative marketing development strategies and priority strategies needed by UUT Agro Semesta in developing Sobean Coffee marketing. The analysis tools used in this study include the IFAS, EFAS, IE, SWOT, and QSPM matrices. The results of the study showed that there were six strength factors, namely Superior Brand, Characteristic dark chocolate and fruity flavors, Red Pick and Honey process, Coffee processing facilities and Assistance from the Kopernik Subak Abian Amertha Karya Foundation as a coffee supplier and five weakness factors, namely Lack of human resources in production and marketing, Marketing is still by word of mouth, Decrease in quality after 3 months, Difficulty finding distributors and Not having a production permit, and four opportunity factors, namely Increasing coffee drink trends, Increasing coffee demand, Export of coffee to international markets and E-commerce and social media and three threat factors, namely Lack of interest in village youth, Relatively expensive prices and Lack of extension workers. The results of the IFAS and EFAS matrix analysis on the SWOT diagram, UUT Agro Semesta has quite strong internal strength but faces quite serious threats, this encourages UUT Agro Semesta to seek alternative strategies that are diversified. There are nine alternative strategies generated from the SWOT matrix, and the results of the QSPM matrix show that creating a UUT development program with the Regional Government and the Kopernik Foundation to attract the interest of village youth is a priority strategy for UUT Agro Semesta in developing Sobean Coffee marketing. Permasalahan yang dihadapi kelompok petani kopi di Tabanan Bali adalah soal pemasaran. Hal ini juga dialami oleh Unit Usaha Tani (UUT) Agro Semesta yang berlokasi di Desa Pajahan, Kecamatan Pupuan, Kabupaten Tabanan. Mereka masih mengalami kesulitan dalam memasarkan produk andalannya, yaitu Kopi Sobean. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor pada lingkungan internal dan eksternal dalam pengembangan pemasaran, serta mencari alternatif strategi pengembangan pemasaran dan strategi prioritas yang diperlukan oleh UUT Agro Semesta dalam mengembangkan pemasaran Kopi Sobean. Alat analisis yang digunakan dalam penelitian ini mencakup matriks IFAS, EFAS, IE, SWOT, dan QSPM. Hasil penelitian menunjukkan bahwa terdapat enam faktor kekuatan yaitu Brand unggulan, Ciri khas rasa dark chocolate dan fruity, Petik merah dan Honey process, Fasilitas pengolahan kopi dan Bantuan dari Yayasan Kopernik Subak Abian Amertha Karya sebagai pemasok kopi dan lima faktor kelemahan yaitu Kurangnya SDM dalam produksi dan pemasaran, Pemasaran masih dari mulut ke mulut, Penurunan kualitas setelah 3 bulan, Kesulitan mencari distributor dan Tidak memiliki izin produksi, serta empat faktor peluang yaitu Trend minuman kopi yang meningkat, Permintaan kopi yang meningkat, Ekspor kopi pasar internasional dan E-commerce dan media sosial dan tiga faktor ancaman yaitu Kurangnya minat pemuda desa, Harga relatif mahal dan Kurangnya tenaga penyuluh. Hasil analisis matriks IFAS dan EFAS pada diagram SWOT, UUT Agro Semesta memiliki kekuatan internal yang cukup kuat namun menghadapi ancaman yang cukup serius, hal ini mendorong UUT Agro Semesta untuk mencari alternatif strategi yang bersifat diversifikasi. Ada sembilan alternatif strategi yang dihasilkan dari matriks SWOT, dan hasil matriks QSPM menunjukkan bahwa membuat program pengembangan UUT dengan Pemda dan Yayasan Kopernik untuk menarik minat pemuda desa menjadi strategi prioritas untuk UUT Agro Semesta dalam mengembangkan pemasaran Kopi Sobean.